Potentially differential impacts on niche overlap between Chinese endangered Zelkova schneideriana and its associated tree species under climate change - Zhou, Yanrong; Lu, Xin; Zhang, Guangfu (Frontiers in Ecology and Evolution, 2023)
Climate change has a significant impact on the potential distribution for endangered trees. However, to date, little is known about how the endangered trees and main associated ones in different types of subtropical forests respond to climate change. Here, we first selected the endangered Zelkova schneideriana endemic to China and its associated trees as focus species from two subtropical forest communities (i.e. deciduous broad-leaf forest, bamboo and broad-leaf mixed forest) in China, and divided them into two species pairs: Z. schneideriana vs. Celtis sinensis, and Z. schneideriana vs. Phyllostachys edulis. Then, we simulated the three species’ suitable areas under current and future climate scenarios using Maxent based on the occurrence records and environmental variables, and further measured niche overlap between each species pair over time. Our Maxent showed: (1) Temperature-related factors have greater influence on Z. schneideriana than the other factors. The most important factor influencing its population distribution was Min temperature of coldest month (Bio6), followed by Mean diurnal range (Bio2), with the total contribution of 78.9%. (2) Currently, the suitable area of Z. schneideriana was predicted to be 106.50 × 104 km2, mostly located in the subtropical region of China, especially in Anhui, Hubei, Hunan, Jiangsu, and Zhejiang provinces. (3) Its suitable area would decrease and its average migration distance was 19.72 km under 16 future climate scenarios, with the core distribution migrating northeast. (4) There is an asynchrony of potential niche overlap between species pairs. One species pair with C. sinensis will rise in terms of Schoener’s D and I values whereas the other one with P. edulis will decline in the future. This asynchrony can be ascribed to the different future suitable ranges of these focus species as well as their ecological characteristics. Our study provides a new perspective on the conservation for endangered trees and surrounding neighbors in Chinese subtropical forests.